The rope swing - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (UK Oxford reading press, 2012)
The children went to the stream where there was a rope swing. Wilf and Biff climbed on the swing while Chip pushed Wilf. Floppy the dog barked at the swinging children. More children took turns on the swing while Floppy continued barking. At the end, Splash! Oh no! Floppy had fallen into the water while looking at the swinging rope.
"The Rope Swing" is a title in the Oxford Reading Tree (ORT) series, typically used for early readers. However, the full formatted content of the book is under copyright and cannot be provided in its entirety.
H3
Building fluency and expression. Recognizing and using common sight words. Understanding story structure (beginning, middle, end). Predicting outcomes based on illustrations and text. Developing vocabulary related to play and nature (e.g., rope, swing, fall, stuck)
Keywords: Supplementary reading material